RESEARCH ON THE RECONDITIONING METAL SPRAYING ULTRASONIC FIELDS - GHEORGHE AMZA; Dan DOBROTĂ; VALENTIN PETRESCU; ZOIA APOSTOLESCU; OANA CHIVU, (Fiabilitate şi Durabilitate)
The paper presents research on process optimization of metal spraying activated ultrasonic fields. In order to optimize process parameters are selected metal spraying flame and flame wire electrode with and without ultrasonic activation. It then makes an analysis of the chemical composition resulting filler material, line and base material for more couplers materials. It also presents the resulting the couple main functional properties for metal oxy-fuel flame spraying and wire electrode with and without activating ultrasonic wire electrode to highlight the advantages of metal spraying process in ultrasonic field.